DEVELOPMENT OF INDIVIDUAL SKILLS OF HIGHLY SKILLED WRESTLERS - Begimkulov Altiboy Jurayevich (Journals Park Publishing, 2022)
This article talks about the classification of the wrestler's general physical fitness and qualities. It was also analyzed that the general physical fitness of a wrestler should be at an excellent level and that each physical quality of a wrestler is closely related to each other.
Keywords: wrestling, training, general physical training, wrestler, individual wrestling, wrestling technique, training, sports games, action games.